Pengaruh Sosial Ekonomi terhadap Perilaku Pengelolaan Sampah Rumah Tangga di Kecamatan Muara Bulian - Adreyan, M. Agung Arkan; M, Damris; Safri, Muhammad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Muara Bulian District is a sub-district in Batang Hari Regency which has the largest population, namely 71.589 people. Based on data from the Batang Hari Regency Environmental Service, waste production in 2022 in Batang Hari Regency will reach an average of 132 tons per day, of which 63,25% of the waste produced will come from household waste. Socioeconomics is thought to be a factor that influences household waste management behavior. The research location was carried out in Muara Bulian sub-district. Primary data was obtained using a data collection tool in the form of a questionnaire. Data were processed using SPSS with logistic regression testing. Based on the results of research and data processing using logistic regression, it was found that the gender and knowledge variables had a significant influence on household waste management behavior. Meanwhile, the variables age, education, employment and income do not have a significant influence on household waste management behavior.